Heads We Win--The Cognitive Side of Counterinsurgency (COIN) RAND Counterinsurgency Study--Paper 1 - Gompert, David C. (RAND Corporation, 2007)
Current U.S. counterinsurgency strategy is in need of stronger cognitive capabilities that will enable the United States to "fight smarter." These include comprehension, reasoning, and decisionmaking, the components that are most effective against an enemy that is quick to adapt, transform, and regenerate. This paper offers concrete ideas for gaining the cognitive advantage in anticipating and countering the new global insurgency.